The Test We Can"”and Should"”Run on Facebook - Crawford, Kate (The Atlantic, 2014)
In 1959, the sociologist Edward Shils wrote an influential essay called “Social Inquiry and The Autonomy of the Individual.” He discussed the nature of studying humans with new techniques—which, for him, included concealed cameras, microphones, and forms of “chemical and psychological manipulation.” These could be powerful tools, but they came at a great cost: There is no doubt that some social scientists, with their zeal for novelty, will be attracted by the possibilities offered by these means of manipulating the external and internal lives of other persons. It is all the more necessary therefore, that the leading persons in these fields should declare themselves as strenuously and decisively opposed to such tampering with human autonomy. Shils expresses many of the anxieties and conundrums we’ve heard this week about massive human studies on networked platforms.